Political Dimension of Policy Implementation in Rufus Giwa Polytechnic, Owo, Ondo State, Nigeria - Dare Ezekiel Arowolo; A. A. Agagu (European Scientific Journal, ESJ, 2020)
Despite the importance of higher education and the role it plays in national development, higher education is experiencing downward trends in Ondo State, Nigeria. This perhaps explains the proliferation of literature on higher education subsector but there has to date been little systematic evaluation of the consequences of political influence on policy implementation in Rufus Giwa Polytechnic, Owo. This article assesses the political context of policy implementation in Rufus Giwa Polytechnic, Owo. Using qualitative method, this article finds evidence of political interference in the implementation of recruitment and funding policies of the polytechnic as the major factor responsible for the low performance in the polytechnic. The findings are relevant both for understanding the political context of policy implementation and also for providing the necessary strategies for effective policy implementation in the polytechnic in particular and higher education subsector in Ondo State, Nigeria in general.